2 - Géophilosophie et déterritorialisation chez Gilles Deleuze : esquisse d’une nouvelle citoyenneté dans l’espace public postnational: https://doi.org/10.4314/ad.v35i4.70215 - Aliana, Serge Bernard Emmanuel (Africa Development, 2021)
In a clear break with traditional metaphysics, which conceived of the human subject in terms of a hypostatic Ego that is stable, rational, self- identical, self-aware, autonomous and assigned to a place or a ‘Polis’ with circumscribed standards, G. Deleuze, through the conceptual prism of ‘Geophilosophy’ rethought the destinal condition of mankind in a new way. Drawing inspiration from the Nietzschean categories of the tragic and the Dionysian, Deleuze attempted to remove the foundation of the rational subject dear to classical philosophy and advanced the idea of a subject that is irrational, aestheticized, dehistoricized, delocalized, mobile, flexible, plural, decentred, fed by a ‘rhizomatic’ identity and open to the flows of the world. To the extent that these flows are always random and mutating and that decentring denies any stable identity or place of assignation. Deleuze outlined a real policy of hybridism, no- madism, wandering and exile that constantly highlighted ‘lines of flight’ as a principle of ‘deterritorialization’. Indeed, what is deterritorialization if not ‘causing flows to travel in a free state, on a desocialized body without organs’. By removing the human subject from rigid institutional frameworks and established state powers, Deleuze intends to emanci- pate it from all ‘codes’ to allow it to express its decoded desires. The focus is therefore on the liberation of desire as a ‘schizophrenic proc- ess’. According to Deleuze, the universal future, i.e. history, is aimed at ‘desiring production in its liberation f om social production’. Thus, desire is a source of deterritorialization.